2017
DOI: 10.1177/0954405417740923
|View full text |Cite
|
Sign up to set email alerts
|

Modeling, microstructure, and mechanical properties of dissimilar 2017A and 5083 aluminum alloys friction stir welds

Abstract: Dissimilar aluminum alloy plates of 2017A-T451 and 5083-H111 were friction stir welded in a butt joint configuration along the longitudinal direction. Welding trials demonstrated that placing 5083 on the advancing side enhanced material flow and consequently formed a larger weld nugget. Numerical simulation supported this observation through analysis of volumetric flow rates through reference planes surrounding the stir zone. The analysis also suggests that the weld configuration that results in a decreasing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…We have also to mention that no clear detail on precipitate evolution in dissimilar welding have been reported in previous chapters. Indeed, literature review seldom report simulations of precipitate evolution when two aluminium grades or even metallic alloys are considered despite the large interest of dissimilar welding as investigated by Hamilton et al (2019). In a recent review article, Patel et al (2019) highlight also the advantages, difficulties and challenges associated to dissimilar aluminium welding in FSW processes.…”
Section: B Growth/dissolution Kinetics Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…We have also to mention that no clear detail on precipitate evolution in dissimilar welding have been reported in previous chapters. Indeed, literature review seldom report simulations of precipitate evolution when two aluminium grades or even metallic alloys are considered despite the large interest of dissimilar welding as investigated by Hamilton et al (2019). In a recent review article, Patel et al (2019) highlight also the advantages, difficulties and challenges associated to dissimilar aluminium welding in FSW processes.…”
Section: B Growth/dissolution Kinetics Estimationmentioning
confidence: 99%
“…In recent years, the scientific community seems particularly interested in the study of dissimilar welding as shown by Hamilton et al (2019). Indeed, FSW process has the advantage to develop welding on alloys usually considered as non-weldable until now.…”
Section:  Dissimilar Weldingmentioning
confidence: 99%
“…Numerical simulation concerning temperature and flow stress in the stir zone for dissimilar FSW has been recently published. 21 However, the yet unaddressed modelling of process forces for dissimilar FSW has been included and experimentally validated in the current analysis.…”
Section: Introductionmentioning
confidence: 99%
“…4 Some benefits of using bimetallic composites are increase wear resistance, lighter weight, appropriate thermal and electrical conductivity, lower spring back and better formability of the sheet. 57…”
Section: Introductionmentioning
confidence: 99%